Stationary soap films with vertical potentials. (February 2022) - López, Rafael; Pámpano, Álvaro
Abstract: We classify cylindrical surfaces in the Euclidean space whose mean curvature is a n th-power of the distance to a reference plane. The generating curves of these surfaces, called n -elastic curves, have a variational characterization as critical points of a curvature energy generalizing the classical elastic energy. We give a full description of such curves obtaining, in some particular cases, closed curves including simple ones.